Electrocatalysts: Building Electron/Proton Nanohighways for Full Utilization of Water Splitting Catalysts (Adv. Energy Mater. 16/2020). Issue 16 (28th April 2020) - Yang, Gaoqiang; Yu, Shule; Kang, Zhenye; Li, Yifan; Bender, Guido; Pivovar, Bryan S.; Green, Johney B.; Cullen, David A.; Zhang, Feng‐Yuan
Abstract : In article number 1903871, Feng‐Yuan Zhang and co‐workers report an innovative electrode design which features mesoporous nanolayer catalysts that significantly augment the accessible electrochemical reaction sites and catalyst utilization for water splitting and hydrogen production. The multilayer‐electrode structure exhibits highly efficient electron and proton transport for improved performance; and may enable inexpensive and earth‐abundant electrocatalysts.